Arthritis in mice induced by a single immunisation with collagen. - Kato, F (1996)
OBJECTIVE: To determine whether collagen induced arthritis (CIA) in mice can be satisfactorily induced by a single immunisation and whether this model has some advantages compared with conventional CIA, which is induced by two immunisations. METHODS: The incidence of arthritis was observed under different immunisation conditions (variation of species of Mycobacterium included in complete Freund's adjuvant and the method of emulsification) and immunological, histopathological, and pharmacological features were examined. RESULTS: Under optimum immunisation conditions, joint inflammation developed two to three weeks after the primary immunisation with an incidence of 100% at four to five weeks. The progression of the arthritis was mild and was associated with moderate increases in concentrations of serum IgG against type II collagen. This CIA model was similar to the conventional model in histopathological and pharmacological features. CONCLUSIONS: Murine CIA could be successfully induced by a single immunisation. An important feature of this model was a mild progression of joint inflammation. This feature seems to be of benefit for monitoring the development of arthritis from an early stage in the disease and for the development of novel antirheumatic drugs for such early stage patients.